D.A. PRIGOV'S POEM "KULIKOVO FIELD" WITHIN THE HISTORICAL-LITERARY TRADITION - Vakhitov Yulay Salavatovich (Western European Studies, 2025)
This article examines D.A. Prigov's poem "Kulikovo Field" within the broad sweep of historical-literary tradition, with particular emphasis on its intricate connections to Alexander Blok's cycle "On Kulikovo Field" and ancient Rus' literary monuments. We delve into Prigov's masterful deployment of antinomies and compositional techniques, alongside his rich intertextual dialogues, including parallels with icon painting and "The Tale of the Mamai Massacre." The analysis reveals that Prigov's apparent "anti-patriotism" is, in fact, meticulously constructed upon a profound cultural dualism, wherein the "Russians-Tatars" opposition unpacks the deeper internal contradictions inherent within Russian culture itself.
Keywords: D.A. Prigov; Kulikovo Field; A.A. Blok; composition